Beyond Assault Trajectory of Rape in Pakistan (Journal of Gender and Social Issues, 2025)
Rape – article 375 has become a non-compoundable and non-bailable offense in Pakistan under the Criminal Laws (Amendment) Act, 2021. It is critical and highly sensitive social subject that is inadequately addressed and mishandled by the system. It emerges from the historical subjugation of women and the structural dominance of men – systemic failures and perceptions of society. Another aspect of rape culture is the pathologizing of victims, declaring them mentally unstable – attention seeking in superficial language. The stigma around discussion on sexual violence is perpetuated by how it is viewed. The course of action on rape has faced structural undermining to the extent of penalizing the victims. This paper studies the stigmas as myths and victim-blaming as rape apology –embedded in cultural convictions related to the status of women and can be analyzed in how women were treated as mere objects aimed at sexual and domestic gratification.
Keywords: Pakistan; Rape Culture; Sexual Violence; Victim Blaming; Women